Implementasi Metode TOPSIS Untuk Penentuan Finalis Duta Wisata Joko Roro Kabupaten Malang (Studi Kasus : Paguyuban Joko Roro) - Krisna Andryan Syahputra Effendi; Edy Santoso; Nurul Hidayat (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Each district and the cities in Indonesia have a separate icon to showcase their respective regions. Start from the culture until the potential of tourism object. One of the most well known icon until the territory was visited by many tourists is tourism object. This is shown by the number of domestic tourists and also foreign tourists who visited in each area in Indonesia one of the Malang Regency. Malang Regency rich natural tourism potential and other tourism. Therefore this Regency nicknamed "The Heart of East Java". Malang Regency has tourism ambassador, joko roro Kabupaten Malang. Joko roro stand since 2005. But in the participants who later became the next joko and roro, the committee feel difficulties. This is marked with the number of participants that resulted in missing data. And also very obstructionist opinion judges when the determination of the finalists who will be joko and roro. From these problems, then designed a decisions support systems can determine the decision of the finalists tour ambassador joko roro of Malang Regency. This research uses namely with one of method TOPSIS and using the five criteria for administration and five criteria for selection. Testing the accuracy of the obtained accurate until 52%.